GLOBALAUZATION AND SPREAD OF ENGLISH - Qodirov Halillullo; Qambaraliyeva Durdona Nodirbek kizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: This article is about the role of English in industry. Explains the reason for the spread of English in Great Britain and the history of globalization of English